2017
DOI: 10.1563/aaid-joi-d-16-00104
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Bovine Bone-Autogenic Bone Mixture Versus Platelet-Rich Fibrin for Maxillary Sinus Grafting: Histologic and Histomorphologic Study

Abstract: Numerous grafting materials have been used to augment the maxillary sinus floor for long-term stability and success for implant-supported prosthesis. To enhance bone formation, adjunctive blood-born growth factor sources have gained popularity during the recent years. The present study compared the use of platelet-rich fibrin (PRF) and bovine-autogenous bone mixture for maxillary sinus floor elevation. A split-face model was used to apply 2 different filling materials for maxillary sinus floor elevation in 22 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 23 publications
1
23
0
5
Order By: Relevance
“…Importantly, the maturation of this type of material may take up to 8 months before implants can be safely placed in maxillary sinus, which might be considered a disadvantage of this material. To mitigate this shortcoming, the addition of growth factors, particularly L‐PRF, to the graft material has been suggested as an alternative approach to increase bone formation, enhance implant stability, favor osseointegration, and accelerate tissue maturation and healing …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Importantly, the maturation of this type of material may take up to 8 months before implants can be safely placed in maxillary sinus, which might be considered a disadvantage of this material. To mitigate this shortcoming, the addition of growth factors, particularly L‐PRF, to the graft material has been suggested as an alternative approach to increase bone formation, enhance implant stability, favor osseointegration, and accelerate tissue maturation and healing …”
Section: Discussionmentioning
confidence: 99%
“…To mitigate this shortcoming, the addition of growth factors, particularly L-PRF, to the graft material has been suggested as an alternative approach to increase bone formation, enhance implant stability, favor osseointegration, and accelerate tissue maturation and healing. 1,18,21,22,[28][29][30]34,35,44,45,[47][48][49][50][51][52] CBCT is considered a reliable technique for the 3D visualization of graft volume changes after sinus augmentation. In this study, we performed three different CBCTs at different time points: immediately after the bone graft, and after 4 and 8 months of healing.…”
Section: Bone Histomorphometry Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…In rabbits, sinus floor augmentation combining PRF with DBM or collagenated heterologous bone did not result in any benefit in terms of bone regeneration (Peker, Karaca & Yildirim, ). Moreover, in sheep a mixture of bovine and autologous bone performed better than PRF, as confirmed by histomorphometry findings (Ocak, Kutuk, Demetoglu, Balcioglu & Ozdamar, )…”
Section: Resultsmentioning
confidence: 54%
“…In group 1, bovine and autogenous bone mixture; and in group 2, PRF was used. The results of this study showed that bovine bone and autogenous bone mixture is superior to PRF as a grafting material in sinus-lifting procedures [34]. According to the results of this study, it may be suggested that PRF should not be used alone in sinus-lift procedure.…”
Section: Animal Studiesmentioning
confidence: 69%